2019
DOI: 10.1080/02687038.2019.1581916
|View full text |Cite
|
Sign up to set email alerts
|

Priming sentence comprehension in aphasia: effects of lexically independent and specific structural priming

Abstract: Purpose.-Impaired message-structure mapping results in deficits in both sentence production and comprehension in aphasia. Structural priming has been shown to facilitate syntactic production for persons with aphasia (PWA). However, it remains unknown if structural priming is also effective in sentence comprehension. We examined if PWA show preserved and lasting structural priming effects during interpretation of syntactically ambiguous sentences and if the priming effects occur independently of or in conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
12
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 74 publications
8
12
1
3
Order By: Relevance
“…Even when PWAs showed robust abstract priming for transitives in Experiment 1, they showed an average of only 4% of verb-specific enhancement on priming. These results are consistent with our previous comprehension priming study, wherein PWAs showed only abstract priming during interpretation of syntactically ambiguous sentences (Lee, Hosokawa, et al, 2019). Furthermore, the findings suggest that the lexically independent and lexically specific structural priming effects are associated with distinctive cognitive processes (Chang et al, 2012;Reitter et al, 2011) and can be selectively affected in PWAs.…”
Section: Predictorssupporting
confidence: 92%
See 4 more Smart Citations
“…Even when PWAs showed robust abstract priming for transitives in Experiment 1, they showed an average of only 4% of verb-specific enhancement on priming. These results are consistent with our previous comprehension priming study, wherein PWAs showed only abstract priming during interpretation of syntactically ambiguous sentences (Lee, Hosokawa, et al, 2019). Furthermore, the findings suggest that the lexically independent and lexically specific structural priming effects are associated with distinctive cognitive processes (Chang et al, 2012;Reitter et al, 2011) and can be selectively affected in PWAs.…”
Section: Predictorssupporting
confidence: 92%
“…This two-step priming might have encouraged the participant to better encode and reuse the lexical-semantic materials of the prime. Different from Yan et al's findings, we (Lee, Hosokawa, et al, 2019) failed to find a lexical boost effect during comprehension of syntactically ambiguous sentences. However, the PWAs still demonstrated abstract priming not only in the immediate priming condition (0-lag) but also over two intervening utterances (2-lag).…”
contrasting
confidence: 99%
See 3 more Smart Citations